Reklama v českých zemích v 19. století jako příklad akulturačního přenosu hospodářské inovace - Jaroslav Stuchlík (AntropoWebzin)
The study explains some aspects of thedevelopment of Czech modern advertising in the19th century. The study uses an analysis of the discourseabout the content of the term “reklama”(ie advertising). Author criticizes professionallyunsubstantiated thesis about historical origin ofCzech modern advertising, which appear in theprimary and secondary literature. The study rejectsthe concept of local development Czech advertising.According to the author it is necessary tocombine emergence advertising (in the 19th century)with the process of acculturation. Processof acculturation began in the fi rst half of the 19thcentury. Transfer of innovation took place in thedirection from the center to the periphery. Thetraditional form of the offers of goods was mainlyverbal, vocal and audio vocal. Acculturation reactionhas brought preferences of visual and literaryforms. Acculturation was also a confl ict betweenhigh and low culture.